Detection of Escherichia coli and E. coli O157 in Veal Mincemeat in Baghdad - Methaq G. Abd Al-Rubaey (Kufa Journal for Veterinary Medical Sciences, 2016)
In order to investigate the prevalence of Escherichia coli and E. coli O157 in veal mincemeat, thirty pooled samples (three replicates from each type, n=90) were randomly collected from different markets and butcher shops in Baghdad during April until August (2015), in which they processed and analyzed by different food microbiological procedures. The results showed isolation and identification of 27 (90%) isolates out of 30 pooled samples as 13 (86.7%) isolates from 15 locally butcher shops mincemeat, in which the serotype O157 was detected in 5 (33.4%) samples; and 14 (93.4%) isolates from 15 imported veal meat (minced locally for human consumption), in which 7 (46.7%) isolates were identified as a serotype O157. The mean log count of E. coli to E. coli O157 in locally produced mincemeat range from 2.845 to 5.602 log10 cfu g_1, while in imported ones range from 4.778 to 8.954 log10 cfu g_1. Results profile provide useful information on biosafety and hazard analyses critical control points of hygienic measurements of E. coli and E. coli O157 in mincemeat marketed in Baghdad.